Complexities of Management of Atypical Ventricular Fibrillation Storm in a Young Patient With TANGO2 - M. Cecilia Gonzalez Corcia; Catherine Bradshaw; Efstathia Chronopoulou; Jennifer Shortland; Benjamin O’Sullivan; Tim Murphy (Case Reports in Pediatrics)
TANGO2 deficiency disorder, a rare autosomal recessive genetic disorder characterised by biallelic loss-of-function variants in the TANGO2 gene, was first described in 2016. This disorder involves the transport and Golgi organisation homologue, impacting Golgi membrane redistribution into the endoplasmic reticulum. Clinically, affected individuals exhibit a multiorgan phenotype, with prominent neurological manifestations such as developmental delay and regression. Metabolic crises, triggered by minor infections or fasting, are a hallmark of the disorder. We present the case of a 5-year-old boy diagnosed with TANGO2 deficiency disorder who experienced a refractory-to-treatment ventricular arrhythmia storm. The patient’s clinical course was marked by rhabdomyolysis-induced muscle pain, weakness and dark urine. Despite aggressive medical management during intercurrent illness, including hyperhydration, maintenance of normoglycemia and correction of electrolyte abnormalities, the patient’s condition deteriorated, leading to a life-threatening ventricular arrhythmia storm. In a life-saving therapeutic approach, the patient underwent a thoracoscopic left sympathectomy during extracorporeal membrane oxygenation (ECMO) support. Remarkably, this intervention resulted in the termination of the ventricular arrhythmia storm. The case underscores the challenges in managing TANGO2 deficiency disorder-associated complications and highlights the potential role of innovative interventions, such as sympathectomy during ECMO, in critical and refractory cases. This case contributes to the understanding of the clinical spectrum of TANGO2 deficiency disorder and emphasises the need for further research into targeted therapies for this rare metabolic condition, where current treatment strategies focus on symptom management.